Effects of a Moderately Lower Temperature on the Proliferation and Degranulation of Rat Mast Cells - Ruoyu Wang; Xiaoqin Yin; Hui Zhang; Jiwei Wang; Lin Chen; Jingwen Chen; Xiaodong Han; Zou Xiang; Dongmei Li (Journal of Immunology Research)
Mast cells are traditionally considered as key effector cells in IgE-mediated allergic diseases. However, the roles of mast cells have also been implicated in diverse physiological and pathological processes. Mast cells are distributed in various organs and tissues of various species. Some of the organs and tissues, such as testis, skin, and the upper part of the respiratory tract, have a temperature that is lower than the body’s core temperature. The purpose of the present study was to investigate the effects of a lower temperature on the proliferation and degranulation of rat mast cells. Here, we demonstrate that cell growth was retarded at 35°C compared to 37°C for both rat peritoneal mast cells (RPMC) and RBL-2H3, a rat mast cell line. Furthermore, RPMC became more susceptible to degranulation at 35°C compared to 37°C. In contrast, degranulation of RBL-2H3 was not as sensitive to temperature change as RPMC. The functionality of mast cells in unique organs with a lower temperature warrants further analysis.